(untitled) - Bromfield, Richard (Hoboken, N.J., 2007)
This readable guide for therapists and therapists-in-training lays out the theoretical essence and practical essentials of doing child and adolescent psychotherapy from the referral call to the last goodbye.
Keywords: Child psychotherapy,Psychotherapy,Tâm lý trẻ em,Tâm lý trị liệu; Methods,Phương pháp